Phosphorus application rates affect the grain yields of different phosphorus-tolerant rice cultivars by regulating grain filling and leaf senescence characteristics - Danke Zhang; Yuyang Li; Hairun Li; Haojing Li; Xihui Zhao; Jing Cao; Guowei Xu (Plant, Soil and Environment)
The grain filling and physiological traits of different phosphorus-tolerant rice cultivars and phosphorus fertiliser rates have not been fully studied. A pot-growth experiment with cv. Lianjing 7 (weak phosphorus tolerance) and cv. Yongyou 2640 (strong phosphorus tolerance) was conducted using four phosphorus rates, namely, 0 (P0), 0.44 (P1), 0.88 (P2), and 1.32 g/pot (P3). Results indicated that grain yield, net photosynthetic rate, soil and plant analyser development (SPAD) value, superoxide dismutase (SOD) and catalase (CAT) activity in leaves, and adenosine diphosphate glucose pyrophosphorylase (AGPase) and sucrose synthase (SuSase) activity in grains increased and then decreased with increasing phosphorus fertiliser rate, whereas malondialdehyde (MDA) content in leaves decreased first and then increased. The above indexes of cv. Lianjing 7 and cv. Yongyou 2640 were optimal at P2 and P1 treatments, respectively. The grain yield, net photosynthetic rate, SPAD value, AGPase content, SuSase content in grains, and SOD and CAT activity in the leaves of cv. Yongyou 2640 were higher, whereas the MDA content was lower than those of cv. Lianjing 7. Correlation analysis showed that AGPase and SuSase activity in superior and inferior grains, photosynthetic rate, and SOD and CAT activity in the leaves were significant or highly significantly positively correlated with grain-filling rate and rice yield. Therefore, the adoption of appropriate phosphorus fertiliser rates can increase the activity of enzymes related to starch synthesis in different phosphorus-tolerant rice, enhance antioxidant systems in leaves at the filling stage, reduce leaf MDA content, and delay leaf senescence. These effects are beneficial to grain filling and increase grain yield.